Upper bound for the crossing number of Qn×K3 - Suebsriwichai A. (2017)
© 2017 by the Mathematical Association of Thailand. All rights reserved. In this paper, we describe a method of finding the upper bound for the crossing Number of Q n ×K 3 . We construct a drawing of Q n × K 3 , called a 3−axes drawing of Q n ×K 3 . A 3 −axes drawing of Q n ×K 3 is a representation of Q n × K 3 on the plane such that its vertices are placed on 3 straight lines L i where i = 1, 2, 3 with a fixed vertex ordering.